Endovascular Treatment With or Without Intravenous Thrombolysis for Acute Ischemic Stroke Due to Tandem Occlusion: A Systematic Review and Meta‐Analysis - Yaowen Hu; Xin Jiang; Yanbo Li; Chuang Yang; Mengmeng Ma; Jinghuan Fang; Li He (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Endovascular treatment (EVT) has been demonstrated to be effective for patients with tandem occlusion. The efficacy and safety of intravenous thrombolysis before EVT in patients with tandem occlusion remain debatable. Methods and Results We conducted a systematic review and meta‐analysis with PubMed, EMBASE, and the Cochrane Library from inception to September 2023. The primary outcome was functional independence, defined as a modified Rankin Scale score of 0 to 2 at 90 days. The secondary outcomes included the successful recanalization rate, symptomatic intracerebral hemorrhage, and mortality at 90 days. In total, 9 studies with 1838 enrolled participants were identified. Our results showed that, compared with treatment with EVT alone, intravenous thrombolysis before EVT was associated with a greater proportion of functional independence at 90 days (odds ratio [OR], 1.39 [95% CI, 1.14–1.69]; P=0.001), a greater rate of successful recanalization (OR, 1.45 [95% CI, 1.11–1.89]; P=0.007) and decreased mortality (OR, 0.68 [95% CI, 0.50–0.93]; P=0.02). Furthermore, there was no significant difference in symptomatic intracerebral hemorrhage between the intravenous thrombolysis plus EVT group and the EVT alone group (OR, 1.16 [95% CI, 0.79–1.70]; P=0.45). Conclusions In patients with acute ischemic stroke and tandem occlusion, intravenous thrombolysis before EVT was associated with a greater rate of favorable functional outcomes and successful recanalization and a lower mortality rate without an increased risk of symptomatic intracerebral hemorrhage compared with patients receiving EVT alone.